Trade, productivity and welfare effects of regional integration in South Asia - Islam, Amirul (Curtin University, 2014)
The thesis examines the impacts of the South Asian free trade agreement (SAFTA) on trade, productivity, and welfare of the member countries. When theoretically relevant variables are controlled for, it is found that the agreement is not effective in creating intra-regional trade flows and improving productivity of the region. India and Nepal gain welfare in the long run, while the others lose. Deeper integration, embracing factor flows, is required to make the agreement fruitful.